The Impact of Hybrid Blended Learning on Learning Motivation among University Students: A PLS-SEM and IPMA Analysis - Sutisna, Didi; Megiati, Yunita Endra; Pratiwi, Noor Komari; Basir, Rizki Rizkyatul (Manunggal Halim Jaya, 2025)
The advancement of information technology has transformed higher education, leading to the adoption of blended learning—a combination of online and offline instruction. This study examines the impact of blended learning on learning motivation and identifies key motivational indicators for improvement. A quantitative survey was conducted with 115 fifth-semester students from the Informatics Engineering Study Program at Universitas Indraprasta PGRI, Jakarta. Data were collected using a validated and reliable five-point Likert-scale questionnaire and analyzed with Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Map Analysis (IPMA) via SmartPLS software. Results indicate that blended learning has a positive and significant effect on students’ learning motivation. IPMA findings indicate that “Flexibility of Time and Place” is the primary area for improvement, followed by Learning Interaction and Learning Effectiveness. At the same time, the Availability of Learning Facilities is a lower priority. Enhancing flexibility is expected to increase motivation substantially. These findings contribute to the development of student-centered learning models and offer practical guidance for educators and policymakers in designing more adaptive and engaging higher education learning environments.